Climate Resilience in Africa : The Role of Cooperation around Transboundary Waters - World Bank Group (World Bank, Washington, DC, 2018)
Addressing water-challenges is central to building climate resilience. In Africa, all major waters are transboundary making cooperation on international waters critically important to building climate resilience. Regional-national coordination is needed if the full range of options for building resilience is to be considered. Furthermore, experience shows that cooperative action can outweigh transaction costs, bring about efficiency gains, and change behavior of cooperating countries to be more future-oriented, leading to an expansion of potential resilience benefits in the longer term. This report draws on a substantial body of empirical evidence from five major basins in Africa - including the Nile, Zambezi, Limpopo, Lake Chad, Niger basins - to support the critical role of transboundary cooperation on water resources management to building systemic resilience to climate change in Africa.